2014
DOI: 10.4250/jcu.2014.22.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Investigation of the Mechanism Underlying Abnormal Interventricular Septal Motion after Open Heart Surgery

Abstract: BackgroundAbnormal interventricular septal motion (ASM) is frequently observed after open heart surgery (OHS). The aim of this study was to investigate the incidence and temporal change of ASM, and its underlying mechanism in patients who underwent OHS using transthoracic echocardiography (TTE).MethodsIn total, 165 patients [60 ± 13 years, 92 (56%) men] who underwent coronary bypass surgery or heart valve surgery were consecutively enrolled in a prospective manner. TTE was performed preoperatively, at 3--6-mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 21 publications
0
18
0
1
Order By: Relevance
“…In the previous study, they showed the incidence of ASM after open heart surgery retrospectively and they found valve surgery is more likely to cause ASM than coronary artery bypass surgery. In this study, the authors demonstrated the incidence of ASM with regular follow-ups, prospectively 9). There was no report about the chronological sequence of ASM in patients with open heart surgeries.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…In the previous study, they showed the incidence of ASM after open heart surgery retrospectively and they found valve surgery is more likely to cause ASM than coronary artery bypass surgery. In this study, the authors demonstrated the incidence of ASM with regular follow-ups, prospectively 9). There was no report about the chronological sequence of ASM in patients with open heart surgeries.…”
mentioning
confidence: 70%
“…There was no report about the chronological sequence of ASM in patients with open heart surgeries. The authors serially checked the incidence and fate of ASM in patients underwent open heart surgery 9). Interestingly, it appeared about 70% of patients immediately after the open heart surgery.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Kang et al . describe a clinically insignificant change in LV function and the presence of abnormal septal motion being largely transient with only 15% of those identified having ongoing abnormal motion at one year although these data are limited by the loss of follow‐up to almost a third of patients and the limited use of some strain parameters. Alternatively, Roshanali et al .…”
Section: Haemodynamic Consequences Related To the Presence Of Septal mentioning
confidence: 99%
“…Несмотря на многочисленные публикации [2,6,12,13], в ранее проведенных исследованиях не акцентировалось внимание на исходное состояние систолической функции левого желудочка или в большинстве работ исследуемая группа включала пациентов с относительно сохранным функциональным состоянием левого желудочка. Настоящая работа посвящена изучению влияния феномена постоперативной МЖП на результаты операции коронарного шунтирования у особой группы пациентов -больных ишемической болезнью сердца, осложненной выраженной дисфункцией левого желудочка (с фракцией выброса ЛЖ 35% и менее).…”
unclassified